Unseen Struggles: Emotional Quotient in the Shadow of Parental Absence - Abcede, Blossom Dalyn; Racadag, Natalie Dhel; Tecson, Zelwin Sam; Alvarez, Diane Lyne; Gamboa, Gabriel Allen; Uy, Daniel Philip; Serapon, Ginella Angelica; Ibañez, Mercedes; Ramos, Rowena Imelda; Panague , Dionnel (12th International Scholars Conference 2025, 2026)
This study examined how the emotional quotient (EQ) of high school students at AUP Academy was affected by parental absence, specifically that caused by employment abroad. Introducing the needs of students navigating non-traditional caregiving arrangements requires an understanding of how parental absence impacts teenage emotional development. Methods: To assess Emotional Quotient in five areas—self-awareness, self-regulation, social skills, empathy, and motivation—a descriptive-correlational methodology was utilized. Students who had one or both parents employed overseas were among the participants. Data were gathered using validated instruments and analyzed using correlation and regression techniques. Findings: Despite the physical absence of one or both parents, the results established that students generally depicted high EQ scores. Nevertheless, correlational analysis reported a weak negative relationship between parental absence and EQ, suggesting that increased absence was associated with slightly lower EQ scores. Linear regression further showed that parental absence modestly predicted lower emotional functioning, particularly in empathy and motivation. Significance: These results demonstrate emotional resilience and particular responses of adolescents whose parents are not present. The study underscores how fostering emotional well-being requires regular emotional support, whether from parents, guardians, or academic staff. The recommendations include training caregivers, promoting open communication with parents, reinforcing guidance services, and providing school-based emotional intelligence programs. Future research should examine the roles of peer support and socio-economic factors in adolescent emotional development.